Alignment parameters of foveal cones - Gorrand, Jean-Marie; Doly, Michel (Journal of the Optical Society of America. A, Optics, image science, and vision, 2009)
In the fovea we measured the orientation and directional characteristics of photoreceptors with an optical technique in a group of 29 subjects. At 6 deg eccentricity, we determined the direction of the normal to the inner limiting membrane (ILM) by analyzing light reflected specularly by the ILM. We found a strong correlation between the orientation of photoreceptor axes and the direction of the normal to the ILM. Therefore, we cannot answer the question of the mechanism of photoreceptor alignment without taking into account the direction of the normal to the underlying retinal pigment epithelium, in addition to phototropic and apodization processes. For a wavelength of 532 nm, the mean value of the directionality factor rho was 0.212 mm(-2) (SD: 0.026 mm(-2)) when measured at the fovea (2 deg sample field). We look for reasons likely to explain the discrepancy between rho values given by different optical methods.